THE EVOLUTION OF HUMAN RESOURCE MANAGEMENT: THE NECESSITY OF FACING THE INDUSTRIAL REVOLUTION 4.0 - Idrus, Syech; Jihan, Jihan; Rahman, Akhmad Setyo; Arta, Deddy Novie Citra; Kespandiar, Tengku (KOMITMEN: Jurnal Ilmiah Manajemen, 2023)
The management of human resources in today’s organizations presents a challenge from a strategic perspective. In order to successfully usher in the era of the Industrial Revolution 4.0, it is essential to realign the new business culture with the empowerment of behavior and performance that is required as part of the individual and organizational learning process. The purpose of this study is to investigate how human resource management has developed in response to Industry 4.0. This research is qualitative, and it employs a qualitative approach in conjunction with a descriptive methodology. The findings of the study indicate that human resource management is a strategic partner for organizations, which in turn generates optimism within those organizations in light of the fourth industrial revolution and VUCA. This study investigates the various epochs in the development of HRM, beginning with personnel management and moving on to human resource management and finally human capital management.